2019
DOI: 10.1038/s41467-019-11494-1
|View full text |Cite
|
Sign up to set email alerts
|

A family of anti-Bacteroidales peptide toxins wide-spread in the human gut microbiota

Abstract: Bacteria often produce antimicrobial toxins to compete in microbial communities. Here we identify a family of broad-spectrum peptide toxins, named bacteroidetocins, produced by Bacteroidetes species. We study this toxin family using phenotypic, mutational, bioinformatic, and human metagenomic analyses. Bacteroidetocins are related to class IIa bacteriocins of Gram-positive bacteria and kill members of the Bacteroidetes phylum, including Bacteroides , Parabacteroides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 60 publications
4
55
0
1
Order By: Relevance
“…may utilize various transporters (such as ABC exporters) to actively secrete the toxins to the environment of their microbial targets. 38 Several of the diffusible toxins produced by Bacteroides spp. have membrane attack complex/perforin (MACPF) domains.…”
Section: Antimicrobial Toxins Are Used In Bacterial Competitionmentioning
confidence: 99%
“…may utilize various transporters (such as ABC exporters) to actively secrete the toxins to the environment of their microbial targets. 38 Several of the diffusible toxins produced by Bacteroides spp. have membrane attack complex/perforin (MACPF) domains.…”
Section: Antimicrobial Toxins Are Used In Bacterial Competitionmentioning
confidence: 99%
“…Accordingly, these common predominant bacteria also played a crucial role in the host's nutrient absorption and immune defense, such as synthesizing glycoside hydrolase and polysaccharide lyase, promoting the degradation of the fibrosome, fructose, starch, etc., and providing the five-carbon or six-carbon sugars [36,38]; the bacterial components (such as LPS [39]) and metabolites (such as SCFAs [40,41], antimicrobial peptides [6,42], etc.) were important in the regulating host energy metabolism and intestinal development and maintaining intestinal epithelial integrity etc.…”
Section: The Relationship Between the Host And Common Dominant Bacteriamentioning
confidence: 99%
“…Analyses of recent human fecal isolates of Bacteroidales with interesting phenotypes revealed that many are resistant to both tetracycline and erythromycin (60, 65) and therefore are not amenable to genetic manipulation using available genetic tools for these bacteria. We evaluated tetracycline and erythromycin resistance among 120 Bacteroides strains from our collection isolated between 2009 and 2011 from the stool of 15 healthy U.S.-resident adults with no history of gastrointestinal diseases (Fig.…”
Section: Resultsmentioning
confidence: 99%